MANAJEMEN PEMBELAJARAN BERBASIS INFORMASI DAN TEKNOLOGI (IT) DI SMK PROFESIONAL PADANG - Wiwita, Risma; Handayani, Revi; Vratiwi, Septiana; Rahman, Antoni; Mayeni, Riska (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
The study reviews it-based learning management in SMK Profesional Padang. The purpose of this study is to find out how the image of it based learning management in SMK Profesional Padang. This research approach is qualitative. The source of data on this study is the principal for students, and the teacher. The data gathering technique used in this studyis observation, interview and documentation. The data analysis technique uses Mileas and Huberman models, that is, data collection, data condensing, data presentation and deduction drawing. Verification of data using triangulation technique. Research shows that the image of eit-based learning management in SMK Profesional Padang, comptrolling the 3 types of learning management are online, blended learning, and offline. Blended learning is prepared a long time ago before the completion and has taken place in several classes but is not optimal because only half of the teachers who have been performing their classes and live streaming, some of them listening in rooms and at home and blended with an lms or zoom and could be in the teacher’s class instructing students to open their smartphone. While offline learning is based on the learning technology that is supported by the existence of the tech tools used in offline learning